Digital Labor and Digital Capitalism: A Critical Political Economy Perspective - Fuchs, Christian (The Handbook of Digital Labor)

Discounts or Donations – The Effectiveness of Different Keep Rewards in Product Return Management - Horsthemke, Johanna; Böhm, Eva (Proceedings of the 2025 AMA Winter Academic Conference)

Exploring students’ constructions of data-based decision trees after an introductory teaching unit on machine learning - Fleischer, Yannik; Biehler, Rolf (ZDM – Mathematics Education)
Abstract This study explores how high school students construct decision trees using data cards and the software CODAP (codap.concord.org) in interviews after attending a teaching unit. We conceptualized data-based decision tree construction using nine key aspects that we intended to teach, tested variations of two design elements in teaching, and analyzed the interviews qualitatively to compare student behavior to intended outcomes. We found high alignment to intentions but also deviations in data activities and informal or context-based rather than data-based reasoning. The design element of context-free (blinded) data seems to enhance data-based reasoning, while the design element of data card use showed diagnostic potential.

Enhancing Blockchain Efficiency via Median Rule - Showmik, Md Jannatul Baki

Berufliche Kompetenzen für nachhaltiges Wirtschaften – Status quo und Herausforderungen in der betrieblichen Ausbildung - Hufnagl, Julia; Kiepe, Karina; Annen, Silvia (Berufsbildungsforschung. Rezeption – Translation – Transfer.)

Transformative Forschung zur Berufsbildung für nachhaltige Entwicklung – Bedeutung und Funktion der Wissenschaft - Kiepe, Karina; Schlömer, Tobias (Berufsbildungsforschung. Rezeption – Translation – Transfer.)

Disability im schulischen Kontext. Über den Umgang von Lehrpersonen - Schlierkamp, Marie Luise (#schuleverantworten)
Spätestens seit der Ratifizierung der UN-Behindertenrechtskonvention und der Formulierung der Menschenrechte ist ein Bekenntnis zur Inklusion ein zentrales Thema in der Schule, in der Ausbildung angehender Lehrkräfte und in der Bildungspolitik. Der Umgang mit Kindern und Jugendlichen mit und ohne Beeinträchtigung in einer heterogenen Klassengemeinschaft einer Regelschule kann Herausforderungen im beruflichen Alltag einer Lehrperson mit sich bringen. Da inklusive schulische Bildung ebenso wie der Anspruch auf Teilhabe in der Gesellschaft zwei Rechte sind, die alle Personen der Gesellschaft einfordern dürfen, bedarf es neben einer positiven Haltung gegenüber Diversität und Vielfalt auch bestimmten Rahmenbedingungen, um unterschiedlichen Bedarfen von Schüler*innen mit Beeinträchtigungen gerecht zu werden.
Keywords: Inklusion; Disability; Umgang mit Diversität und Vielfalt im Kontext Beeinträchtigungen

Lerngegenstand, Modellierung, religionsdidaktisch - Reis, Oliver (WiReLex 02/2025)

Zeros and exponential profiles of polynomials I: Limit distributions, finite free convolutions and repeated differentiation - Jalowy, Jonas; Kabluchko, Zakhar; Marynych, Alexander (arXiv:2504.11593)
Given a sequence of polynomials $(P_n)_{n \in \mathbb{N}}$ with only nonpositive zeros, the aim of this article is to present a user-friendly approach for determining the limiting zero distribution of $P_n$ as $deg\, P_n → ∞$. The method is based on establishing an equivalence between the existence of a limiting empirical zero distribution $μ$ and the existence of an exponential profile $g$ associated with the coefficients of the polynomials $(P_n)_{n \in \mathbb{N}}$. The exponential profile $g$, which can be roughly described by $[z^k]P_n(z) ≈ \exp(n g(k/n))$, offers a direct route to computing the Cauchy transform $G$ of $μ$: the functions $t \mapsto tG(t)$ and $α \mapsto \exp(-g'(α))$ are mutual inverses. This relationship, in various forms, has previously appeared in the literature, most notably in the paper [Van Assche, Fano and Ortolani, SIAM J. Math. Anal., 1987]. As a first contribution, we present a self-contained probabilistic proof of this equivalence by representing the polynomials as generating functions of sums of independent Bernoulli random variables. This probabilistic framework naturally lends itself to tools from large deviation theory, such as the exponential change of measure. The resulting theorems generalize and unify a range of previously known results, which were traditionally established through analytic or combinatorial methods. Secondly, using the profile-based approach, we investigate how the exponential profile and the limiting zero distribution behave under certain operations on polynomials, including finite free convolutions, Hadamard products, and repeated differentiation. In particular, our approach yields new proofs of the convergence results `$\boxplus_n → \boxplus$' and `$\boxtimes_n → \boxtimes$', extending them to cases where the distributions are not necessarily compactly supported.

Von Transzendenz zum Transhumanismus. Deutungskulturen von (Un-)Heilsgeschichte im 19. und 20. Jahrhundert

Propagation of Chaos and Residual Dependence in Gibbs Measures on Finite Sets - Jalowy, Jonas; Kabluchko, Zakhar; Löwe, Matthias (Mathematical Physics, Analysis and Geometry)
Abstract We compare a mean-field Gibbs distribution on a finite state space on N spins to that of an explicit simple mixture of product measures. This illustrates the situation beyond the so-called increasing propagation of chaos introduced by Ben Arous and Zeitouni [3], where marginal distributions of size $$k=o(N)$$ k = o ( N ) are compared to product measures.

Optimal transport of stationary point processes: Metric structure, gradient flow and convexity of the specific entropy - Erbar, Matthias; Huesmann, Martin; Jalowy, Jonas; Müller, Bastian (Journal of Functional Analysis)

Comparative Analysis of Evolutionary Algorithms for Energy-Aware Production Scheduling - Burmeister, Sascha Christian; Rogalski, Till Niklas; Schryen, Guido

„Religiöse Gewalt“ in der Frühen Neuzeit? Eine begriffsgeschichtliche Revision - Süßmann, Johannes (Religiöse Gewalt in historischer Dimension)
In this chapter the common parlance of “religious violence in early modern history” is put to the test, although it seems to be linked in an indissoluble way with the master narratives about this period. The first section shows that it makes no difference whether historians think of early modern history in terms of impersonal structures or of personal experience–they agree in regarding religion as a crucial cause of violence. Against this widespread conviction the paper unfolds two arguments. The first is that the Latin word “religio”, as it was used throughout the 16th and 17th century, did not mean ‘religion’ in our modern comprehensive understanding of the word. Instead its meaning was quite narrow and specific, referring either to the medieval sense of ‘committing oneself to God by joining a religious order’ (becoming a “religiosus” resp. a “religiosa”) or to the ancient sense of ‘scrupulously venerating God’. It did not mean ‘faith’, ‘doctrine’, ‘worship’, ‘church law’ or ‘denomination’, and definitely not all these things in conjunction. Only when the vernacular languages began to borrow the Latin word from the 16th century onwards was its narrow meaning broadened. As a consequence of reformation and counterreformation, the idea arose that one should make faith and doctrine and worship and church law match, although the attempt to implement this new rapport provoked much opposition and turned out to be a very violent process. From this point of view what is generally called “early modern religious violence” is violence caused not by religion, but by the ambition to establish a new idea of religion. The second argument is that our modern understanding of religion is coined by the 18th-century critique of religion. Only the Enlightenment’s claim to overcome religion (in the new sense of the word) declared it to be “irrational” or even “fanatic”. Thus the Enlightenment invented religious fanatism, using it as a retrospective explanation of the violence that had gripped the last centuries. Modern parlance of “religious violence” unintentionally prolongs a very poor idea of religion–and one that should not be mistaken for an explanation.
Keywords: Religion; Gewalt; Begriffsgeschichte; Frühe Neuzeit; Aufklärung; Religionskritik

Unternehmensbewertung als Verknüpfung von Investitions- und Finanzierungsprogramm - Uhde, André (Unternehmerische Finanzierungspolitik – eine wertorientierte Einführung)

Ermittlung der Kosten des Eigen- und Fremdkapitals - Uhde, André (Unternehmerische Finanzierungspolitik – eine wertorientierte Einführung)

Relevanz und Wertbeitrag der Kapitalstruktur - Uhde, André (Unternehmerische Finanzierungspolitik – eine wertorientierte Einführung)

Wirtschaftswissenschaftliche Forschungsrichtungen vor der Neoklassik - Uhde, André (Institutionenökonomie und Betriebswirtschaftslehre)

Grundlagen der Principal-Agent-Theorie - Uhde, André (Institutionenökonomie und Betriebswirtschaftslehre)

Unternehmerische Finanzierungspolitik - Eine wertorientierte Einführung